Microencapsulation of a putative probiotic Enterobacter species, C6‐6, to protect rainbow trout, Oncorhynchus mykiss (Walbaum), against bacterial coldwater disease. Issue 1 (1st October 2014) - Ghosh, B; Cain, K D; Nowak, B F; Bridle, A R
Abstract: Flavobacterium psychrophilum is the causative agent of bacterial coldwater disease (BCWD), which has a major impact on salmonid aquaculture globally. An Enterobacter species, C6‐6, isolated from the gut of rainbow trout, Oncorhynchus mykiss (Walbaum), has been identified as a potential probiotic species providing protection against BCWD. This study examined the effects of alginate microencapsulation on the protective efficacy of C6‐6 against BCWD in vivo when administered to rainbow trout fry orally or by intraperitoneal (IP) injection. Viable C6‐6 bacteria were microencapsulated successfully, and this process (microencapsulation) did not significantly deteriorate its protective properties as compared to the administration of non‐microencapsulated C6‐6 bacteria. Both oral and IP delivery of C6‐6 achieved significantly better protection than control treatments that did not contain C6‐6 bacteria. The highest relative percent survival (RPS) resulted from IP delivery (71.4%) and was significantly greater than the highest oral RPS (38.6%). Successful intestinal colonization was not critical to protective effects of C6‐6. The study showed that C6‐6 administration, with or without encapsulation, was a viable choice for protecting fry from BCWD especially when administered intraperitoneally.